Using the fact that log a - log b = log a/b:
log4 (x² + 3x)/(x + 5) = 1
Then getting rid of the logs by exponentation by 4:
(x² + 3x)/(x + 5) = 4^1 = 4
Multiply both sides by (x + 5):
x² + 3x = 4(x + 5) = 4x + 20
Combine on one side:
x² -x - 20 = 0
Factor:
(x - 5)(x + 4) = 0
x - 5 = 0, so x = 5, or
x + 4 = 0, so x = -4
Check:
log4 (5² + 3(5)) - log4 (5 + 5) = 1
log4 (25 + 15) - log4 10 = 1
log4 40 - log4 10 = 1
log4 4(10) - log4 10 = 1 (then using log 4(10) = log 4 + log 10)
log4 4 + log4 10 - log4 10 = 1
log4 4 = 1 = 1, check!
log4 (4² +3(-4)) - log4(-4 + 5) = 1
log4 4 - log4 1 = 1
1 - 0 = 1, check!
2007-01-02 09:32:19
·
answer #1
·
answered by Jim Burnell 6
·
0⤊
0⤋
log4 (x^2+3X) - log4 (x+5) =1
<=> log4 (x^2+3x) = 1 + log4 (x+5)
<=> log4 (x^2+3x) = log4 [4(x+5)]
<=> x^2 + 3x = 4x + 20 and x > -5
<=> x^2 - x -20 = 0 and x > -5
<=> x = 5 or x = -4 and x > -5
so x =5 or x = -4
2007-01-02 09:53:15
·
answer #2
·
answered by James Chan 4
·
0⤊
0⤋
Rule: log?(x) - log?(y) = log?(x/y) log?(x) = y ? x = a^y log?(x²+3x) - log?(x+5) = a million log?((x²+3x) / (x+5)) = a million (x²+3x) / (x+5) = 4¹ = 4 x² + 3x = 4(x+5) = 4x + 20 x² - x + 20 = 0 (x - 5)(x + 4) = 0 x = -4, 5 Neither of those solutions violate the area of the unique function, the argument of a log can not be damaging or 0. as a result they are the two ultimate.
2016-11-25 23:19:36
·
answer #3
·
answered by ? 4
·
0⤊
0⤋
Remember that log(a) - log(b) = log(a/b); the rule holds regardless of the base.
log[4]( (x² + 3x) / (x+5) ) = 1
Raise both sides upon the base 4; the log disappears on the left.
(x² + 3x) / (x+5) = 4^1 = 4
Multiply both sides by (x+5) to get it out of the denominator:
x² +3x = 4(x +5)
Expand out:
x² + 3x = 4x + 20
Put everything on the left:
x² - x - 20 = 0
Factor:
(x - 5)(x + 4) = 0
The solutions are x = 5 and x = -4.
Double-checking:
log[4] (5² + 3(5)) - log[4](5 + 5) =?
log[4] (40) - log[4] (10) =?
log[4] (40/10) =?
log[4](4) = 1 <-- check
log[4] ((-4)² + 3(-4)) - log[4](-4 + 5) =?
log[4] (16 - 12) - log[4](1) =?
log[4] (4) - log[4](1) =?
log[4](4) - 0 =?
log[4](4) = 1 <-- check
So the answers are:
x = 5 or x = -4
2007-01-02 09:35:24
·
answer #4
·
answered by Puzzling 7
·
2⤊
0⤋
log4(x²+3x) - log4(x+5) = 1
log4[(x²+3x)/(x+5)] =1
Apply inverse logarithmic function:
[(x²+3x)/(x+5)] =4^1
(x²+3x)/(x+5)=4
x²+3x = 4(x+5)
x²-x-20=0
Solving the last quadratic equation, we get:
x1 = 5
x2 = -4
That's it!
Good luck!
2007-01-02 09:41:45
·
answer #5
·
answered by CHESSLARUS 7
·
0⤊
0⤋
(x^2+3x)/(x+5)=4
x^2+3x=4x+20
x^2-x-20=0
(x-5)(x+4)=0
x=5 or -4
2007-01-02 09:33:43
·
answer #6
·
answered by raj 7
·
0⤊
0⤋